La inversión extranjera directa y el desarrollo humano en los países de América latina en el periodo 2000-2020. - Gamarra Cela, Karina Leonela (2023)
Foreign direct investment has been seen as the engine of development in host countries, enabling workers to adapt to new knowledge and technologies by improving their efficiency, it also contributes to improving the quality of life by creating jobs and increasing tax revenues that contribute to greater economic growth. In this sense, the objective of this research is to determine the relationship between foreign direct investment and human development in Latin American countries, during the period 2000-2020. For this, a fixed effects model was used, composed of a panel of data from 14 Latin American countries. In this way, it was obtained as a result that, faced with an increase in FDI, there is an increase in human development by 0.021%; and it was found that the variables have a balance relationship in the long term, coinciding with research by other authors, which determined a positive relationship between investment and development. Therefore, it was concluded that the investment had a decreasing behavior due to the COVID-19 pandemic, while human development showed a growing trend due to the improvement of the quality of life during the last years. This research is developed in the following chapters: Chapter I, consists of the introduction, the approach to the problem and the objectives; Chapter II, includes the background, where previous research on the subject is detailed, and the theoretical basis for foreign direct investment and human development. Chapter III covers the methodology consisting of the approach, method, type and techniques of research, in addition to population and sample, variables and the formulation of the econometric model; finally, Chapter IV, shows the results of the data collected on the variables and the application of the fixed effects model by the time section.